Role of tilt-table testing in syncope diagnosis and management: analysis of patients referred to a syncope unit. (25th November 2020) - Castelo, A; Laranjo, S; Lousinha, A; Cunha, P; Brandao, C; Alves, S; Silva, A; Ferreira, V; Bras, P; Mano, T; Oliveira, M; Ferreira, R
Abstract: Introduction: Head-up tilt-testing (HUT) enables the reproduction of reflex syncope in a laboratory setting. Despite being used to confirm the diagnosis of this syncope, there is some concerns regarding the best protocol to use and recent studies with implantable loop recorders have called the value of HUT into question. Aim: To characterize the population undergoing HUT according to the modified Italian protocol, type of response to HUT and subsequent management at our center in the last 4 years. Methods: Retrospective analysis of consecutive P who underwent HUT between 2015 and 2018. Descriptive analysis of patients (P) demographics and medical history, indication for HUT, type of response to HUT and management. Results: A total of 419P (55.1% female) were included with a mean age of 62 years. The majority (n=302, 72.1%) had comorbidities (structural heart disease – 55%, cardiac dysrhythmias – 57.6%, hypertension – 48.3%, diabetes – 15.6%, depression – 15.9%, cerebrovascular disease –10.6%) or was under medication (n=220, 52.5%) with a potential hypotensive or bradycardic effect (44.1% ACEI/ARA, 29.1% beta-blocker, 27.7% diuretic, 23.6% antidepressant, 22.7% calcium channel blocker, 19.1% benzodiazepines). Syncope/presyncope episodes accounted for 56.1% of the HUT, with falls and disequilibrium accounting for 52%. In 21 cases (5%) suspected dysautonomia or other non-specified reasons were the indication for HUT. HUT were ordered according to the guidelines in 136P (84.6% – indication level I, 3.6% – level IIa, 11.8% – level IIb). HUT was positive in 292P (69.7%) – 77.1% after nitroglycerin administration (vasodepressor – 170P, cardioinhibitory – 53P, mixed – 62P and dysautonomic – 7P). Cardioinhibitory (CI) response predominated in the younger, and vasodepressor in the older P. Of the P with CI response, 41.5% had asystole (median of 41.4s, minimum 7.5s, maximum 115s). All P were instructed in the need to avoid triggering factors and perform counterpressure maneuvers. A pacemaker was implanted in 24P (5.7% of all population, due to long sinus pauses and asystole). Twenty-four P (5.7%) completed a tilt training program. Conclusion: Most of the HUT were requested for syncope/presyncope, frequently according to the guidelines. There was a high rate of positive tests, with a predominance of vasodepressive response, particularly in the elderly. Funding Acknowledgement: Type of funding source: None